Rearrangement by inversion of a T-cell receptor delta variable region gene located 3' of the delta constant region gene. - Korman, A J (1989)
We have located a T-cell receptor variable (V) delta gene segment immediately 3' of the delta constant (C) region gene and 5' to the known joining (J) alpha gene segments. This V delta gene is in the opposite transcriptional polarity to C delta and has rearranged to C delta by inversion in a gamma/delta-expressing hybridoma, DN7.3. This V delta gene is commonly rearranged in adult but not fetal gamma/delta-expressing thymocytes and has not been observed among alpha gene rearrangements reported to date. The reciprocal joining sequence isolated from this cell line contains N region nucleotides between the recombination signal sequences, in contrast to previously analyzed reciprocal joints. The results are discussed in the context of models accounting for ordered V gene usage during lymphocyte development.